Houndsley and Catina - Howe, James 1946-; Gay, Marie-Louise (Cambridge, Mass Candlewick Press, 2006)
Houndsley and Catina run into trouble when they decide to prove that they are the best at cooking and writing, respectively
A Junior Library Guild selection
Keywords: Cats -- Juvenile fiction; Dogs -- Juvenile fiction; Friendship -- Juvenile fiction; Cats -- Fiction; Dogs -- Fiction; Friendship -- Fiction